Turnaround Strategies during Performance Decline in Indonesian Manufacturing Firms - Ganto, Jullimursyida (UI Scholars Hub, 2008)
The study examines causes of performance decline and turnaround strategies of Indonesia following the 1997/1998 financial crisis. The sample chosen was from the large manufacturing firms in Indonesia. The result of this study found that competitive changes, poor management, high cost structure, economic changes and failure of major projects were the significant factors contributing to the performance decline during the crisis of 1997/1998, while restructuring strategies was important strategies adapted to turnaround firms.